Measuring the Role of Compensation as an Intermediary Variable in Measuring the Relationship between Management Talent and Employee Effectiveness - Tafsir, Muhammad; Husain, Nurjanna Hayati; Shaari, Roziana (BASKARA : Journal of Business and Entrepreneurship, 2023)
This study aimed to determine the effect of Talent Management moderated by Compensation on Employee Work Effectiveness. The sample in this study were employees at Aerotel Smile Hotel Makassar City. There are 50 employees as a sample. Three variables are used: talent management as an independent variable, employee effectiveness as the dependent variable, and Compensation as an intervening variable. This study uses a descriptive method with a quantitative approach, where data collection is done through interviews and questionnaires. The analysis tool used is Partial Least Square. While taking samples, the author uses the entire population. Data were obtained through interviews and distributing questionnaires to determine the influence of talent management and employee work effectiveness by making Compensation an intervening variable. The study results show that Talent Management positively and significantly affects Employee Work Effectiveness. Talent Management moderated by Compensation has a Positive and Significant Effect on Employee Work Effectiveness. In the future, the next researcher can add environmental conditions as a variable that affects work effectiveness.